The Role of Islamic Mass Organizations In The History Of Cultural In South Sulawesi (1905-1998) - Ainun Syafitri Muslimin; Safriadi (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This article explores the role of Islamic mass organizations in the historical development of Islam in South Sulawesi, Indonesia, from 1905 to 1998. The study examines how these organizations shaped the region's religious life and socio-cultural transformation. This study uses a qualitative literature review approach to analyze historical documents, scholarly publications, and organizational archives related to key Islamic organizations. The findings reveal that the emergence of Islamic mass organizations was strongly influenced by growing sentiments of patriotism and nationalism during the colonial and post-colonial periods. These organizations Sarekat Islam, Nahdlatul Ulama, Muhammadiyah, and Wahdah Islamiyah—significantly promoted religious awareness, fostered community development, and strengthened social cohesion in South Sulawesi. Each organization followed distinct strategies based on its doctrinal orientation and cultural context, yet all contributed to increasing public engagement with Islamic teachings. This study highlights the crucial role of Islamic civil society in shaping regional religious identity and socio-political dynamics in Indonesia.